Outpatient Foley catheter induction protocol provides clinical and cost benefits. Issue 4 (5th July 2021) - Washburn, Mary C.; Washburn, Mark; Hong, Christina; Roth, Patrick; Richter, Paula
Abstract: Background: Obstetric induction procedures are expensive, and little is known of the specific difference in cost between inpatient and outpatient protocols for these procedures. Objective: The objective of this study was to examine the difference in health care costs, maternal and neonatal morbidity, and cesarean birth rates for inpatient versus outpatient Foley induction protocols. Material and methods: We conducted a retrospective study using deliveries from 2013 to 2015 that received an outpatient or inpatient Foley catheter induction. Inductions were matched by race, parity, and maternal age. We used univariate and multivariate logistic regression to test the association between type of induction, length of stay, and cost. Maternal and neonatal factors and cesarean rates were also considered. Results: A total of 163 outpatient Foley inductions were matched 1:1 to inpatient inductions. Outpatient inductions were more likely to have a shorter length of hospitalization from admission to discharge (a 7.17‐hour difference, 95% CI, 71.00, 77.59) and lower costs of hospitalization (408 per patient, 95% CI, 4305, 4714). In the univariate analysis, there was no difference in rate of cesarean birth (OR 0.95, 95% CI, 0.61, 1.48). However, in the multivariate analysis, there was a decreased rate of cesarean for outpatient inductions (OR 0.5, 95% CI, 0.26, 0.97). Conclusions: Outpatient Foley catheter induction appears to be a safe, cost‐effective method for induction of labor. Generating protocols allowing patients to receive quality care in an outpatient setting is increasingly important in current health care environments.